Revitalizing Public Training Centers in Indonesia : Challenges and the Way Forward - World Bank (Jakarta, 2014)
The goal of this report is to examine the effectiveness and efficiency of the public vocational training centers (Balai Latihan Kerja, hereinafter BLK) in Indonesia. Its findings and recommendations will contribute to the ongoing effort of the Ministry of Manpower and Transmigration (MoMT) to revitalize the BLK training system. There are wide variations in terms of the size and capacities of BLK operating at central, provincial and district levels. This is indicated by the average number of graduates from the centers at each of these different levels in 2009, with 1,300 centrally managed BLK, compared with only around 650 and 340 at the provincial and district levels respectively. The variation in the average number of graduates may indicate deep differences in the operations of the training centers at the three levels. Due to these differences, various approaches at each of the different levels may be required to improve the centers. The emphasis and orientation of BLK programs has changed since their first establishment. In particular, there has been a continuing growth in community based training and in the activities of the Mobile Training Unit (MTU). This indicates that a large portion of demand for BLK training is from communities in rural areas. Given this, the stagnation or decline of the courses that would be beneficial to the greatest percentage of the working population in these areas, such as courses related to agriculture, agricultural processing, and husbandry and fishery, is of great concern. The national training system is well-established in terms of skills standards and the continuing development of training package by the government to support training activities at BLK. Therefore, the mechanisms and systems for implementing Competency-Based Training (CBT) throughout BLK at the central level are in place.